DESIGN AND IMPLEMENTATION OF A WEB INTERACTIVE THEMATIC CARTOGRAPHY METHOD BASED ON A WEB SERVICE CHAIN - ZENG, XINGGUO; DU, QINGYUN; REN, FU; ZHAO, FEI (Boletim de Ciências Geodésicas, 2013)
There is a tendency toward the creation of thematic maps on the web in the ongoing development of cartographic technology. However, automatically creating maps through the web and creating interactive web maps are two challenges associated with this field. To solve these problems, a web thematic cartography method based on a web service chain is presented here. Automated cartography is performed through knowledge-based web cartographic services, and interacting with the services is possible. The method is implemented in the construction of a urban thematic atlas in Shenzhen, China that is dedicated to supporting decision making for urban planning and public participatory thematic map making on the web.